I can't talk about the trees without the blood - Clark, Tiana (Pitt poetry series., 2018)
"For poet Tiana Clark, trees will never be just trees. They will also and always be a row of gallows from which Black bodies once swung. This is an image that she cannot escape, but one that she has learned to lean into as she delves into personal and public histories, explicating memories and muses around race, elegy, family, and faith by making and breaking forms as well as probing mythology, literary history, her own ancestry, and, yes, even Rihanna. I Can't Talk About the Trees without the Blood, because Tiana cannot engage with the physical and psychic landscape of the South without seeing the braided trauma of the broken past--she will always see blood on the leaves."--Publisher's website